Different volumes of tubes for clonal propagation of Coffea canephora from seedlings - Espindula, Marcelo Curitiba; Balbino, Tony José; Jaraceski, Rutinéia; Teixeira, Alexsandro Lara; Dias, Jairo Rafael Machado; Teixeira, Richelly Gisela Pasqualotto (Coffee Science - ISSN 1984-3909, 2018)
The aim in the present study was to evaluate the growth of Coffea canephora cv. ‘Conilon BRS Ouro Preto’ seedlings in different tube volumes. The experiment was performed at Embrapa Rondônia plant nursery in Ouro Preto do Oeste, Rondônia, Brazil, from July to November 2013. The treatments consisted of five tube volumes (50, 100, 170, 280 and 400 cm3) plus one control composed by polyethylene bags (11 cm width x 20 cm height) with capacity of 770 cm3. The experimental design was a randomized complete block design with 15 replicates, formed by 15 clones that compose the Conilon ‘BRS Ouro Preto’ cultivar. The tube volume of 280 cm3 provide the best vegetative performance of seedlings, similarly to volume of 400 cm3, thus, the use of larger tubes would not justify. Tubes of 50, 100 and 170 cm3 produce seedlings with physiological quality similar to the control until 130 days after staking, but may limit the development of seedlings in a longer period.